(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article traces the dynamics of changes in the approach to the assessment of bi-and multilingualism, summarizes the views of foreign and domestic scientists at the phenomenon of multilingualism in the context of social and political change, as well as a systematic classification of the available types of multilingualism to the situation in their base criteria.